Crime scene photography - Robinson, Edward M. (Elsevier, 2007)
Crime Scene Photography is a book wrought from years of experience, with material carefully selected for ease of use and effectiveness in training, and field tested by the author in his role as a Forensic Services Supervisor for the Baltimore County Police Department. While there are many books on non-forensic photography, none of them adequately adapt standard image-taking to crime scene photography. The forensic photographer, or more specifically the crime scene photographer, must know how to create an acceptable image that is capable of withstanding challenges in court. This book blends the practical functions of crime scene processing with theories of photography to guide the reader in acquiring the skills, knowledge and ability to render reliable evidence.